Competitiveness between ethnic Malays and ethnic Chinese in Malaysia - Yeoh, J. P. S.; Yeoh, P. A. (Global Science and Technology Forum, 2015)
Previous research have compared competitive behaviour between participants of different nationalities, profession and gender. This current research investigates competitive behaviour between a multiethnic sample from Malaysia. Ethnic Malay and ethnic Chinese Malaysians were primed to compete in a singing competition and completed a Revised Competitive Index questionnaire. Results showed that ethnic Chinese were more competitive and enjoyed competing more than ethnic Malays. There were also significant differences in gender with females being more competitive, enjoyed competing and were more contentious than males. These results are discussed in terms of previous research on cultural, socio-political policies and gender sensitivities.